Oral microbiota signature predicts the prognosis of colorectal carcinoma - Shi-Hao Zhou; Yan Du; Wen-Qiong Xue; Min-Jun He; Ting Zhou; Zhi-Yang Zhao; Lu Pei; Yi-Wei Chen; Jin-Ru Xie; Chang-Ling Huang; Yong-Qiao He; Tong-Min Wang; et al. (npj Biofilms and Microbiomes)
Abstract Emerging evidence links oral-derived gut microbes to colorectal cancer (CRC) development, but CRC prognosis-related microbial alterations in oral remain underexplored. In a retrospective study of 312 CRC patients, we examined the oral microbiota using 16S rRNA gene full-length amplicon sequencing to identify prognostic microbial biomarkers for CRC. Neisseria oralis and Campylobacter gracilis increased CRC progression risk (HR = 2.63 with P = 0.007, HR = 2.27 with P = 0.001, respectively), while Treponema medium showed protective effects (HR = 0.41, P = 0.0002). A microbial risk score (MRS) incorporating these species effectively predicted CRC progression risk (C-index = 0.68, 95% CI = 0.61–0.76). When compared to a model constructed solely from clinical factors, including tumor stage, lymphatic metastasis, and perineural invasion, the predictive accuracy significantly improved with the addition of the MRS, resulting in a C-index rising to 0.77 (P = 2.33 × 10−5). Our findings suggest that oral microbiota biomarkers may contribute to personalized CRC monitoring strategies, their implementation in clinical surveillance necessitates confirmatory studies.